Exploring the fear of clinical errors: associations with socio-demographic, professional, burnout, and mental health factors in healthcare workers - A nationwide cross-sectional study - Laurent Boyer; Laurent Boyer; Albert W. Wu; Sara Fernandes; Sara Fernandes; Bach Tran; Bach Tran; Yann Brousse; Tham Thi Nguyen; Tham Thi Nguyen; Dong Keon Yon; Dong Keon Yon; et al. (Frontiers Media S.A., 2024)
BackgroundThe fear of clinical errors among healthcare workers (HCW) is an understudied aspect of patient safety. This study aims to describe this phenomenon among HCW and identify associated socio-demographic, professional, burnout and mental health factors.MethodsWe conducted a nationwide, online, cross-sectional study targeting HCW in France from May to June 2021. Recruitment was through social networks, professional networks, and email invitations. To assess the fear of making clinical errors, HCW were asked: "During your daily activities, how often are you afraid of making a professional error that could jeopardize patient safety?" Responses were collected on a 7-point Likert-type scale. HCW were categorized into "High Fear" for those who reported experiencing fear frequently ("once a week," "a few times a week," or "every day"), vs. "Low Fear" for less often. We used multivariate logistic regression to analyze associations between fear of clinical errors and various factors, including sociodemographic, professional, burnout, and mental health. Structural equation modeling was used to explore how this fear fits into a comprehensive theoretical framework.ResultsWe recruited a total of 10,325 HCW, of whom 25.9% reported "High Fear" (95% CI: 25.0-26.7%). Multivariate analysis revealed higher odds of "High Fear" among males, younger individuals, and those with less professional experience. High fear was more notable among physicians and nurses, and those working in critical care and surgery, on night shifts or with irregular schedules. Significant associations were found between "High Fear" and burnout, low professional support, major depressive disorder, and sleep disorders.ConclusionsFear of clinical errors is associated with factors that also influence patient safety, highlighting the importance of this experience. Incorporating this dimension into patient safety culture assessment could provide valuable insights and could inform ways to proactively enhance patient safety.